Flexible iron-silica carbon composite nanofiber film and preparation method thereof

By forming a composite of the Fe2O3 phase with SiOC material, and using electrospinning and heat treatment processes, a flexible Fe2O3/SiOC nanocomposite fiber film was prepared, which solved the problem of insufficient electromagnetic wave-transmissive performance and mechanical properties of SiOC nanofibers in high temperature environments, and achieved the comprehensive excellent performance of the material.

CN119507125AInactive Publication Date: 2025-02-25NANJING TECH UNIV
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411581680.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-02-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing SiOC nanofibers have insufficient electromagnetic wave-transmissive and mechanical properties in high temperature environments, and have great limitations in the preparation process.

Method used

By forming a composite of the Fe2O3 phase with SiOC material, and using electrospinning process and subsequent heat treatment and oxidation treatment, a continuous flexible Fe2O3/SiOC nanocomposite fiber film was prepared.

Benefits of technology

The flexibility, thermal insulation performance, oxidation resistance and electromagnetic wave transmission performance of the fiber are significantly improved, and the comprehensive excellent mechanical properties and electromagnetic properties of the material are achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119507125A_ABST
    Figure CN119507125A_ABST
Patent Text Reader

Abstract

The invention relates to a flexible iron-silica carbon composite nanofiber film and a preparation method thereof.The preparation method comprises the steps that through an electrostatic spinning preparation method, a precursor and a spinning aid are dissolved in an organic solution, and an iron source compound is added into the spinning solution to obtain a precursor composite nanofiber film; and carrying out non-melting treatment, high-temperature pyrolysis and oxidation treatment on the precursor nanofiber film to finally obtain the Fe2O3 / SiOC composite nanofiber film with a structure that Fe2O3 nanocrystals are dispersed and distributed in SiOC nanofibers. According to the preparation method disclosed by the invention, the modification of the SiOC nanofiber is realized by utilizing an electrostatic spinning process for the first time, and the controllable preparation of the Fe2O3 / SiOC composite nanofiber film is realized. The morphology, the structure and the distribution of the nanofibers are controlled by controlling the concentration, the conductivity, the spinning voltage, the yarn outlet rate, the collection mode and the like of a precursor solution, the size of the nanofibers is changed by changing the compounding amount of an iron phase, and the elemental composition and the phase structure of the nanofibers are controlled by changing the pyrolysis temperature and the oxidation treatment temperature. And the product not only has excellent compression elasticity and heat insulation performance, but also shows excellent high-temperature oxidation resistance, and has very wide practical application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of preparation of new composite fiber materials, and relates to a flexible, heat-insulating and high-temperature oxidation-resistant iron oxide-silicon oxide carbon (Fe2O3 / -SiOC) composite nanofiber film with electromagnetic wave transmission performance and a preparation method thereof. Background Art

[0002] With the rapid development of high-frequency communications, high-performance fiber-reinforced polymer wave transparent materials are not only required to provide effective protection for electromagnetic equipment, but also to be able to perfectly cope with various extreme application environments. It is well known that polymer-derived ceramics (PDC) are a type of electromagnetic wave transmission material with broad application prospects. PDC-SiOC is particularly attractive because of its low dielectric loss to ensure effective transmission of electromagnetic waves, wide-band transmission performance to adapt to different frequency range requirements, strong mechanical properties and high temperature resistance in extreme environments, as well as low density, high strength and low raw material cost, thus showing remarkable application potential in the field of lightweight multifunctional wave-transparent materials that adapt to harsh environments. Chinese patent CN112723356 A has proven the excellent wave-transparent performance of SiOC fiber.

[0003] However, the inherent brittleness of ceramics seriously hinders their application in complex environments. According to reports, researchers have adopted strategies such as microcrack toughening, phase change toughening, and whisker toughening to prepare flexible ceramic membranes or films that can withstand bending to a certain extent. However, these thin films or thin sheets of ceramics are difficult to release external stress when large bending deformations occur, resulting in limited improvement in flexibility. Therefore, the one-dimensionalization and nano-sizing of ceramic materials are the key to improving the flexibility and ductility of materials and reducing the density of materials, which can make ceramic materials more effectively adapt to complex shapes and surfaces, increase the coverage of materials, and thus improve electromagnetic wave transmission performance. Compared with ceramic membranes or ceramic sheets, one-dimensional ceramic fibers have a high aspect ratio and good continuity, which helps to form a three-dimensional continuous network to dissipate external forces, thereby improving flexibility and compression rebound performance, while enhancing the air content inside the fiber film and improving the thermal insulation performance of the fiber film. The SiC nanofibers disclosed in Chinese patents CN 108866810 A and CN 116926785 A, the SiO2 nanofibers reported in SiC@SiO2 / carbon (Journal of Materials Chemistry C 7(48)(2019)15233-15242) and PVC / SiO2 / SiO2@Ag (Journal of Membrane Science 661(2022)), and the SiOC nanowires disclosed in CN 116288759 A and CN 112723356 A have demonstrated the feasibility of one-dimensionalization and nanoscale ceramic materials. However, the improvement of electromagnetic wave transmission performance and mechanical properties (flexibility, compressive strength, thermal insulation performance) of SiOC nanofibers after high-temperature oxidation and the optimization design urgently need to be broken through.

[0004] In the above preparation methods, electrospinning is a new processing method for preparing ultra-fine nanofibers. It is simple to operate, has mild conditions, and is low in cost. It also has a faster preparation speed and efficient production efficiency, and can quickly mass-produce SiOC nanofibers. Nanofibers prepared by electrospinning usually have higher purity and uniformity, which is beneficial to improving the performance and stability of the material. SiOC nanofibers prepared based on electrospinning technology have a larger specific surface area and aspect ratio, and can be designed and achieved by adjusting the spinning process and changing the spinning system. Many good properties. CN114790614B discloses a method for preparing a barium titanate @ titanium dioxide composite nanofiber film by electrospinning, and CN110983623B discloses a composite nanofiber film with a porous surface prepared by electrospinning. The above patents have successfully prepared fiber films with flexibility. However, the products of the above public achievements need to be further improved and explained in terms of flexibility, compression resilience, thermal insulation performance, and efficient electromagnetic wave transmission performance. Summary of the invention

[0005] The purpose of the present invention is to improve the deficiencies of the prior art and to provide a flexible iron-silicon oxygen carbon composite nanofiber film. Another purpose of the present invention is to provide a method for preparing the above-mentioned flexible iron-silicon oxygen carbon composite nanofiber film. In view of the current application advantages and disadvantages of one-dimensional SiOC materials in electromagnetic wave transmission in high temperature environments, as well as the corresponding preparation process limitations, the present invention forms an organic nano-sized composite of Fe2O3 phase and one-dimensional SiOC material, and uses an electrospinning process and subsequent heat treatment and oxidation treatment to prepare a continuous flexible Fe2O3 / SiOC nanocomposite fiber film, and the nanofiber film has excellent electromagnetic wave transmission performance, heat insulation performance and oxidation resistance.

[0006] The technical solution of the present invention is: a flexible iron oxide-silicon oxygen carbon composite nanofiber film, characterized in that: iron oxide Fe2O3 nanocrystals are dispersed in silicon oxygen carbon SiOC nanofibers, the size of iron oxide Fe2O3 nanocrystals is distributed between 2 and 5 nm, and the mass proportion of Fe2O3 nanocrystals in the iron-silicon oxygen carbon composite nanofiber film is 1 to 6%.

[0007] The present invention also provides a method for preparing the above-mentioned flexible iron oxide-silicon oxygen carbon composite nanofiber film, the steps are as follows:

[0008] Step 1: dispersing and dissolving SiOC precursor and a high molecular polymer that is easy to spin in an organic solvent at a mass ratio of (0.6-6):1 to form a solution; wherein the concentration of SiOC precursor in the solution is 0.15 g / mL-0.45 g / mL;

[0009] Step 2: dispersing the iron-containing compound in the solution of step 1 to obtain a uniformly dispersed precursor spinning solution; wherein the weight ratio of the iron-containing compound to the precursor is 20% to 200%;

[0010] Step 3: Place the precursor spinning solution into a syringe, install a stainless steel needle at the front end of the syringe, and then install it into the electrospinning equipment for spinning, wherein the spinning positive voltage is 15-20 kV, the negative voltage is 15-20 kV, the propulsion flow rate is 0.1-0.3 mL / min, the distance between the needle and the collector is 10-15 cm, and the environment is room temperature;

[0011] Step 4: subjecting the precursor nanofiber film collected on the collector to an infusible treatment at a temperature of 160 to 210° C.;

[0012] Step 5: placing the precursor fiber film after the infusibility treatment in a carbon crucible, and then performing a high-temperature heat treatment under a protective atmosphere, wherein the heat treatment temperature is 600-1400°C, and the holding time is 3-5h, to prepare a Fe2O3 / SiOC composite nanofiber film; preferably, the heating rate during the high-temperature heat treatment is 5-10°C / min;

[0013] Step 6: Place the heat-treated fiber film in an alumina crucible and perform oxidation treatment in an air atmosphere to obtain an iron oxide-silicon oxide carbon composite nanofiber film, wherein the oxidation treatment temperature is 600-1600°C and the insulation time is 1h to 3h; preferably, the heating rate during the oxidation treatment is 5 to 10°C / min.

[0014] Preferably, the SiOC precursor is polymethylsilsesquioxane MK or polysiloxane PSO.

[0015] Preferably, the spinnable high molecular polymer is polystyrene PS, polycaprolactone PCL or polyvinylpyrrolidone PVP.

[0016] Preferably, the organic solvent is a mixed solution of one of toluene, chloroform or isopropanol and N,N-dimethylformamide, or a mixed solution of one of tetrahydrofuran or chloroform and xylene; wherein the volume ratio of one of toluene, chloroform or isopropanol to N,N-dimethylformamide is (1-5):1; the volume ratio of one of tetrahydrofuran or chloroform to xylene is 1:(2-3).

[0017] Preferably, the iron-containing compound is ferric nitrate Fe(NO3)2, ferric acetylacetonate Fe(acac)3 or ferrocene.

[0018] Preferably, the collector is a drum collector. Preferably, the inner diameter of the stainless steel needle is 0.51-1.69 mm.

[0019] Beneficial effects:

[0020] The present invention proposes a flexible iron oxide / silicon oxide carbon Fe2O3 / SiOC composite nanofiber film with electromagnetic wave transmission performance, heat insulation performance and oxidation resistance performance and a preparation method thereof. With the introduction of the iron phase and the oxidation treatment of the fiber film, the generated iron oxide Fe2O3 nanocrystals are dispersed and distributed in the structure inside the silicon oxide carbon SiOC nanofiber. On the one hand, the spinning performance of the SiOC precursor is improved, and the finally obtained Fe2O3 / SiOC composite nanofiber has significantly improved fiber diameter, fiber flexibility, heat insulation performance and oxidation resistance compared with pure SiOC fiber; on the other hand, the fiber film after heat treatment is oxidized, which not only further reduces the size of the nanofiber to a great extent, but also promotes the formation of SiO2 fibers and reduces the carbon content in the fiber film, thereby significantly improving the electromagnetic wave transmission performance of the SiOC nanofiber film.

[0021] The present invention realizes for the first time the controllable preparation of Fe2O3 / SiOC composite nanofiber film with comprehensive excellent mechanical properties, thermal insulation properties, oxidation resistance and excellent electromagnetic wave transmission properties by using a simple and low-cost process.

[0022] The morphology, structure and distribution of the nanofibers can be controlled by controlling the concentration and conductivity of the precursor solution, the spinning voltage, the spinning rate and the collection method. The size of the nanofibers can be changed by changing the composite amount of the iron phase. The elemental composition and phase structure of the nanofibers can be controlled by changing the pyrolysis temperature and the oxidation treatment temperature. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 Schematic diagram of the preparation process of Fe2O3 / SiOC composite nanofiber film in Example 1.

[0024] Figure 2 SEM images of the Fe2O3 / SiOC composite nanofiber film in Example 1 after (a) high-temperature heat treatment and (b) oxidation treatment.

[0025] Figure 3 For the implementation of Example 1, the Fe2O3 / SiOC composite nanofiber film (a) is bent; curled; folded; twisted; (b) is freely cut to demonstrate the flexibility of the fiber; and (c) its thermal insulation performance is demonstrated.

[0026] Figure 4 This is a demonstration of the electromagnetic wave transmission performance of the Fe2O3 / SiOC composite nanofiber film in Example 1.

[0027] Figure 5(a) Stress-strain curves of the Fe2O3 / SiOC composite nanofiber film under different compressive strains in Example 1; (b) stress-strain curves after different number of cycles; (c) stress retention and maximum stress after different compressive strain tests.

[0028] Figure 6 This is a demonstration of the thermal insulation performance of the Fe2O3 / SiOC composite nanofiber film in Example 1.

[0029] Figure 7 This is a demonstration of the oxidation resistance of the Fe2O3 / SiOC composite nanofiber film in Example 1. DETAILED DESCRIPTION

[0030] The present invention will now be further described with reference to the embodiments and the accompanying drawings:

[0031] Embodiment 1:

[0032] Follow the flow chart Figure 1 As shown, the specific preparation method process is:

[0033] (1) 2.7 g of polymethylsilsesquioxane MK and 0.9 g of polyvinylpyrrolidone PVP were dissolved in 12 mL of a mixed solution of isopropanol and N,N-dimethylformamide DMF in a volume ratio of 5:1 and magnetically stirred for 2 h until completely dissolved to form a uniform MK / PVP spinning solution.

[0034] (2) Weigh 20% of the weight of MK iron acetylacetonate and add it to the solution of step (1), and stir magnetically for 3 hours to obtain a MK / PVP / Fe mixed spinning solution.

[0035] (3) 10 mL of the solution in step (2) was extracted with a syringe, the inner diameter of the needle was selected to be 0.51 mm, the propulsion speed was 0.3 mL / min, the positive voltage for spinning was 15 kV, the negative voltage was 20 kV, the distance between the nozzle and the collector was 10 cm, the collector type was a drum collector, and the drum speed was 500 r / min. A composite fiber membrane was obtained.

[0036] (4) The precursor composite fiber in step (3) is subjected to an infusibility treatment at a temperature of 160°C.

[0037] (5) The composite fiber after the infusibility treatment in step (4) is subjected to high-temperature pyrolysis treatment, the pyrolysis temperature is 1400° C., the holding time is 3 h, the heating rate is 5° C. / min, and the entire pyrolysis process is protected by argon gas.

[0038] (6) The fiber film after heat treatment in step (5) is oxidized at an oxidation temperature of 1600°C, a holding time of 1h, a heating rate of 5°C / min, and the entire oxidation process is carried out in air; the iron oxide Fe2O3 nanoparticles in the composite nanofiber film are dispersed in the silicon oxygen carbon SiOC nanofibers, and the size of the iron oxide Fe2O3 nanoparticles is 2nm, wherein the mass proportion of the iron oxide Fe2O3 nanocrystals in the Fe2O3 / SiOC composite nanofiber film is 1wt%.

[0039] Figure 1 Schematic diagram of the preparation process of Fe2O3 / SiOC composite nanofiber film. Figure 2 The SEM images of the fiber film (a) after high-temperature heat treatment and (b) after oxidation treatment show that the prepared fibers have been nano-sized and have formed a three-dimensional network structure. After oxidation treatment, the fiber diameter is further reduced and the three-dimensional network structure remains intact. Figure 3 It can be seen that (a) bending; (b) twisting; (c) folding; (d) cutting etc. represent the display of fiber flexibility. Figure 4 This is the demonstration of the wave transmission performance of the oxidized nanofiber film. It can be seen that the material exhibits excellent electromagnetic wave transmission performance. In the 8.2-12.4 band, (a) the real part of the dielectric constant is maintained at a low level, and the value is close to 1.0, (b) the value of tanδ remains stable at a low level, ranging from 0.0004-0.0023, (c) the transmission rate (T) is basically maintained at 99.5%, and the reflectivity and energy consumption of electromagnetic waves are close to 0. Figure 5 (a) Stress-strain curve of nanofiber film under different compressive strains; (b) Stress-strain curve after different number of cycles; (c) Stress retention and maximum stress after different compressive strain tests. It can be seen that after different compressive strain tests, the film material can return to its original position, and after 500 cycles of loading and unloading, it still maintains more than 95% of the maximum compressive stress. Figure 6 The thermal insulation performance of the nanofiber film shows that after being heated on a heating plate at 250°C for 10 minutes, the temperature of the fiber film surface is maintained at around 60.3°C, which forms a huge temperature difference with the 246.1°C on the heating plate surface. Figure 7 This is a demonstration of the oxidation resistance of the Fe2O3 / SiOC composite nanofiber film. When the fiber film is treated in an air environment, the fiber film still maintains excellent flexibility, compression rebound performance and electromagnetic wave projection performance.

[0040] Embodiment 2:

[0041] (1) 5.4 g of polymethylsilsesquioxane MK and 2.7 g of polystyrene PS were dissolved in 12 mL of a mixed solution of toluene and N,N-dimethylformamide DMF in a volume ratio of 1:1 and magnetically stirred for 2 h until completely dissolved to form a uniform MK / PVP spinning solution.

[0042] (2) Weigh 200% of the weight of MK in iron nitrate Fe(NO3)2 and add it to the solution of step (1). After magnetic stirring for 3 hours, obtain a MK / PVP / Fe mixed spinning solution.

[0043] (3) 10 mL of the solution in step (2) was extracted with a syringe, and the inner diameter of the needle was selected to be 1.69 mm, the propulsion speed was 0.1 mL / min, the positive voltage for spinning was 20 kV, the negative voltage was 15 kV, the distance between the nozzle and the collector was 15 cm, the collector type was a drum collector, and the drum speed was 500 r / min. A composite fiber membrane was obtained.

[0044] (4) The precursor composite fiber in step (3) is subjected to an infusibility treatment at a temperature of 210°C.

[0045] (5) The composite fiber after the infusibility treatment in step (4) is subjected to high-temperature pyrolysis treatment, the pyrolysis temperature is 600° C., the holding time is 5 h, the heating rate is 10° C. / min, and the entire pyrolysis process is protected by argon gas.

[0046] (6) The fiber film after heat treatment in step (5) is subjected to oxidation treatment, the oxidation temperature is 600°C, the holding time is 3h, the heating rate is 10°C / min, and the whole oxidation process is carried out in air; the iron oxide Fe2O3 nanocrystals in the composite nanofiber film are dispersed in the silicon oxygen carbon SiOC nanofibers, the iron oxide Fe2O3 nanocrystal size is 5nm, and the mass proportion of the iron oxide Fe2O3 nanocrystals in the Fe2O3 / SiOC composite nanofiber film is 6wt%. After the fiber film is subjected to high temperature heat treatment and oxidation treatment, the prepared fiber has been nano-sized and a three-dimensional network structure has been formed, and after the oxidation treatment, the fiber diameter is further reduced, and the three-dimensional network structure remains intact.

[0047] Embodiment 3:

[0048] (1) 1.8 g of polysiloxane PSO and 0.9 g of polycaprolactone PCL were dissolved in 12 mL of a mixed solution of xylene and chloroform in a volume ratio of 3:1 and magnetically stirred for 2 h until completely dissolved to form a uniform MK / PVP spinning solution.

[0049] (2) Weigh 20% of the weight of ferrocene to the solution of step (1) and stir magnetically for 3 hours to obtain a MK / PVP / Fe mixed spinning solution.

[0050] (3) Use a syringe to extract 10 mL of the solution in step (2), select a needle with an inner diameter of 0.9 mm, a propulsion speed of 0.1 mL / min, a spinning positive voltage of 20 kV, a negative voltage of 15 kV, a distance of 15 cm between the nozzle and the collector, a drum collector, and a drum speed of 500 r / min to obtain a composite fiber membrane.

[0051] (4) The precursor composite fiber in step (3) is subjected to an infusibility treatment at a temperature of 210°C.

[0052] (5) The composite fiber after the infusibility treatment in step (4) is subjected to high-temperature pyrolysis treatment, the pyrolysis temperature is 1400° C., the holding time is 5 h, the heating rate is 5° C. / min, and the entire pyrolysis process is protected by argon gas.

[0053] (6) The fiber film after heat treatment in step (5) is subjected to oxidation treatment, the oxidation temperature is 600°C, the holding time is 3h, the heating rate is 5°C / min, and the whole oxidation process is carried out in air; the iron oxide Fe2O3 nanocrystals in the composite nanofiber film are dispersed in the silicon oxygen carbon SiOC nanofibers, the iron oxide Fe2O3 nanocrystal size is 2nm, and the mass proportion of the iron oxide Fe2O3 nanocrystals in the Fe2O3 / SiOC composite nanofiber film is 3wt%. After the fiber film is subjected to high temperature heat treatment and oxidation treatment, the prepared fiber has been nano-sized and a three-dimensional network structure has been formed, and after the oxidation treatment, the fiber diameter is further reduced, and the three-dimensional network structure remains intact.

[0054] Embodiment 4:

[0055] (1) 1.8 g of polysiloxane PSO and 2.7 g of polystyrene PS were dissolved in 12 mL of a mixed solution of chloroform and N,N-dimethylformamide in a volume ratio of 1:1 and magnetically stirred for 2 h until completely dissolved to form a uniform MK / PVP spinning solution.

[0056] (2) Weigh 200% of the weight of ferrocene in the MK solution and add it to the solution in step (1). After magnetic stirring for 3 hours, obtain a MK / PVP / Fe mixed spinning solution.

[0057] (3) Use a syringe to extract 10 mL of the solution in step (2), select a needle with an inner diameter of 0.51 mm, a propulsion speed of 0.3 mL / min, a spinning positive voltage of 15 kV, a negative voltage of 15 kV, a distance of 10 cm between the nozzle and the collector, a drum collector, and a drum speed of 500 r / min to obtain a composite fiber membrane.

[0058] (4) The precursor composite fiber in step (3) is subjected to an infusibility treatment at a temperature of 160°C.

[0059] (5) The composite fiber after the infusibility treatment in step (4) is subjected to high-temperature pyrolysis treatment, the pyrolysis temperature is 600° C., the holding time is 3 h, the heating rate is 10° C. / min, and the entire pyrolysis process is protected by argon gas.

[0060] (6) The fiber film after heat treatment in step (5) is subjected to oxidation treatment, the oxidation temperature is 1600°C, the holding time is 3h, the heating rate is 10°C / min, and the whole oxidation process is carried out in air; the iron oxide Fe2O3 nanocrystals in the composite nanofiber film are dispersed in the silicon oxygen carbon SiOC nanofibers, the iron oxide Fe2O3 nanocrystal size is 5nm, and the mass proportion of the iron oxide Fe2O3 nanocrystals in the Fe2O3 / SiOC composite nanofiber film is 6wt%. After the fiber film is subjected to high temperature heat treatment and oxidation treatment, the prepared fiber has been nano-sized and a three-dimensional network structure has been formed, and after the oxidation treatment, the fiber diameter is further reduced, and the three-dimensional network structure remains intact.

[0061] Embodiment 5:

[0062] (1) 5.4 g of polymethylsilsesquioxane MK and 0.9 g of polyvinylpyrrolidone PVP were dissolved in 12 mL of a mixed solution of xylene and tetrahydrofuran in a volume ratio of 2:1 and magnetically stirred for 2 h until completely dissolved to form a uniform MK / PVP spinning solution.

[0063] (2) Weigh 20% of the weight of MK iron acetylacetonate and add it to the solution of step (1), and stir magnetically for 3 hours to obtain a MK / PVP / Fe mixed spinning solution.

[0064] (3) Use a syringe to extract 10 mL of the solution in step (2), select a needle inner diameter of 1.69 mm, a propulsion speed of 0.1 mL / min, a spinning positive voltage of 20 kV, a negative voltage of 20 kV, a distance of 15 cm between the nozzle and the collector, a collector type of drum collector, and a drum speed of 500 r / min to obtain a composite fiber membrane.

[0065] (4) The precursor composite fiber in step (3) is subjected to an infusibility treatment at a temperature of 160°C.

[0066] (5) The composite fiber after the infusibility treatment in step (4) is subjected to high-temperature pyrolysis treatment, the pyrolysis temperature is 1400° C., the holding time is 5 h, the heating rate is 10° C. / min, and the entire pyrolysis process is protected by argon gas.

[0067] (6) The fiber film after heat treatment in step (5) is subjected to oxidation treatment, the oxidation temperature is 1000°C, the holding time is 2h, the heating rate is 5°C / min, and the whole oxidation process is carried out in air; the iron oxide Fe2O3 nanocrystals in the composite nanofiber film are dispersed in the silicon oxygen carbon SiOC nanofibers, the iron oxide Fe2O3 nanocrystal size is 3nm, and the mass proportion of the iron oxide Fe2O3 nanocrystals in the Fe2O3 / SiOC composite nanofiber film is 4wt%. After the fiber film is subjected to high temperature heat treatment and oxidation treatment, the prepared fiber has been nano-sized and has formed a three-dimensional network structure, and after oxidation treatment, the fiber diameter is further reduced, and the three-dimensional network structure remains intact.

[0068] Embodiment 6:

[0069] (1) 2.7 g of polymethylsilsesquioxane MK and 0.9 g of polycaprolactone PCL were dissolved in 12 mL of a mixed solution of xylene and tetrahydrofuran in a volume ratio of 2:1 and magnetically stirred for 2 h until completely dissolved to form a uniform MK / PVP spinning solution.

[0070] (2) Weigh 100% of the weight of MK in iron nitrate Fe(NO3)2 and add it to the solution of step (1). After magnetic stirring for 3 hours, obtain a MK / PVP / Fe mixed spinning solution.

[0071] (3) Use a syringe to extract 10 mL of the solution in step (2), select a needle inner diameter of 1.69 mm, a propulsion speed of 0.1 mL / min, a spinning positive voltage of 15 kV, a negative voltage of 20 kV, a distance of 15 cm between the nozzle and the collector, a collector type of drum collector, and a drum speed of 500 r / min to obtain a composite fiber membrane.

[0072] (4) The precursor composite fiber in step (3) is subjected to an infusibility treatment at a temperature of 210°C.

[0073] (5) The composite fiber after the infusibility treatment in step (4) is subjected to high-temperature pyrolysis treatment, the pyrolysis temperature is 1000° C., the holding time is 3 h, the heating rate is 5° C. / min, and the entire pyrolysis process is protected by argon gas.

[0074] (6) The fiber film after heat treatment in step (5) is subjected to oxidation treatment, the oxidation temperature is 1000°C, the holding time is 1h, the heating rate is 5°C / min, and the whole oxidation process is carried out in air; the iron oxide Fe2O3 nanocrystals in the composite nanofiber film are dispersed in the silicon oxygen carbon SiOC nanofibers, the iron oxide Fe2O3 nanocrystals have a size of 3nm, and the mass proportion of the iron oxide Fe2O3 nanocrystals in the Fe2O3 / SiOC composite nanofiber film is 5wt%. After the fiber film is subjected to high temperature heat treatment and oxidation treatment, the prepared fiber has been nano-sized and has formed a three-dimensional network structure, and after oxidation treatment, the fiber diameter is further reduced, and the three-dimensional network structure remains intact.

[0075] Table 1 is a performance comparison of the Fe2O3 / SiOC composite nanofiber films of Examples 1 to 6 and samples from other public literature.

[0076]

Claims

1. A flexible iron oxide-silicon oxygen carbon composite nanofiber film, characterized in that: The iron oxide Fe2O3 nano-crystals are dispersed in the silicon oxygen carbon SiOC nano-fibers, the size of the iron oxide Fe2O3 nano-crystals is distributed between 2 and 5 nm, and the mass proportion of the Fe2O3 nano-crystals in the iron-silicon oxygen carbon composite nano-fiber film is 1 to 6%.

2. A method for preparing the flexible iron oxide-silicon oxygen carbon composite nanofiber film as claimed in claim 1, comprising the following steps: Step 1: dispersing and dissolving SiOC precursor and a high molecular polymer that is easy to spin in an organic solvent at a mass ratio of (0.6-6):1 to form a solution; wherein the concentration of SiOC precursor in the solution is 0.15 g / mL-0.45 g / mL; Step 2: dispersing the iron-containing compound in the solution of step 1 to obtain a uniformly dispersed precursor spinning solution; wherein the weight ratio of the iron-containing compound to the precursor is 20% to 200%; Step 3: Place the precursor spinning solution into a syringe, install a stainless steel needle at the front end of the syringe, and then install it into the electrospinning equipment for spinning, wherein the spinning positive voltage is 15-20 kV, the negative voltage is 15-20 kV, the propulsion flow rate is 0.1-0.3 mL / min, and the distance between the needle and the collector is 10-15 cm; Step 4: subjecting the precursor nanofiber film collected on the collector to an infusible treatment at a temperature of 160 to 210° C.; Step 5: placing the precursor fiber film after the infusibility treatment in a carbon crucible, and then subjecting it to a high-temperature heat treatment under a protective atmosphere, wherein the heat treatment temperature is 600 to 1400° C., and the holding time is 3 to 5 hours; Step 6: Place the heat-treated fiber film in an alumina crucible and perform oxidation treatment in an air atmosphere to obtain an iron oxide-silicon oxygen carbon composite nanofiber film; wherein the oxidation treatment temperature is 600-1600° C. and the insulation time is 1 h to 3 h.

3. The method according to claim 2, characterized in that: The SiOC precursor is polymethylsilsesquioxane MK or polysiloxane PSO.

4. The method according to claim 2, characterized in that: The spinnable high molecular polymer is polystyrene PS, polycaprolactone PCL or polyvinylpyrrolidone PVP.

5. The method according to claim 2, characterized in that: The organic solvent is a mixed solution composed of one of toluene, chloroform or isopropanol and N,N-dimethylformamide, or a mixed solution composed of one of tetrahydrofuran or chloroform and xylene; wherein the volume ratio of one of toluene, chloroform or isopropanol to N,N-dimethylformamide is (1-5):1; the volume ratio of one of tetrahydrofuran or chloroform to xylene is 1:(2-3).

6. The method according to claim 2, characterized in that: The iron-containing compound is iron nitrate Fe(NO3)2, iron acetylacetonate Fe(acac)3 or ferrocene.

7. The method according to claim 2, characterized in that: The collector is a drum collector.

8. The method according to claim 2, characterized in that: The inner diameter of the stainless steel needle is 0.51-1.69 mm.

9. The method according to claim 2, characterized in that: The heating rate during the high temperature heat treatment is 5 to 10° C. / min; the heating rate during the oxidation treatment is 5 to 10° C. / min.

Citation Information

Patent Citations

  • Micron / submicron / nanometer magnetic silicon carbide fiber and preparation method thereof

    CN102199811A

  • Flexible hafnium carbide / silicon carbide composite nano fiber membrane with electromagnetic wave absorption performance and preparation method thereof

    CN108866810A

  • Fe-SiC / C composite nano wave-absorbing fiber and preparation method thereof

    CN113279089A

  • Preparation method of flexible MgAl2O4 nanofiber membrane for chemical warfare agent digestion

    CN113502598A

  • Preparation method of nano-iron-containing SiC fiber

    CN117005064A